On feminism and conflict resolution the participation of moro women towards mediation in Cotabato City - De Asis, Judith Pastor
This study was conducted to unearth, and analyze the participation of Moro women mediators in the barangay justice system. Mediation processes in Western, indigenous, and Islamic contexts does not highlight Moro women?s participation in mediation, their mediation techniques, and the challenges they face as mediators. To address this lack of literature, this research employed a qualitative-phenomenological method to describe the lived experiences of the Moro women as they engage in mediation to settle disputes within their respective barangays. A one-on-one interview among three (3) key participants was conducted in this study. The results revealed that Moro women become a mediator through their family background, recommendations from family members and appointment by barangay officials. Marriage-related and economic-related conflicts are the common disputes being settled at the barangay level. To resolve these disputes, the Moro women mediators commonly use facilitative mediation and med-arb mediation. Mediation in the barangay justice system by Moro women also integrates the local adat in settling disputes. Lastly, the study shows that through mediation, Moro women gain a sense of respect and recognition as they engage themselves in such practice